Framing effects on bribery behaviour: experimental evidence from China and Uganda - Gaggero, Alessio; Appleton, Simon; Song, Lina (Springer, 2018)
In this study we investigate the effect of framing on bribery behaviour. To do this, we replicate Barr and Serra (Exp Econ, 12(4):488–503, (2009) and carry out a simple one-shot bribery game that mimics corruption. In one treatment, we presented the experiment in a framed version, in which wording was embedded with social context; in the other, we removed the social context and presented the game in a neutral manner. The contribution of this paper is that it offers a comparison of framing effects in two highly corrupt countries: China and Uganda. Our results provide evidence of strong and significant framing effects for Uganda, but not for China.